El género y las dimensiones de la justicia: reflexiones sobre la teoría tridimensional de Nancy Fraser - Postigo, Marta (CUADERNOS KÓRE, 2012)
Contemporary feminist theory faces important challenges. Firstly, the central concerns of social justice, such as equity and economic redistribution, are still relevant to the feminist theory which has shifted its attention towards the identity politics and the “cultural turn”. Secondly, in advanced capitalist societies and the globalized world, feminist theory has to deal with gender relations in a context of plurality of claims for recognition and civil movements based on race, ethnicity, cultural belongings and sexual orientation. This article offers a critical reflection on Nancy Fraser’s theory that attempts to integrate the two paradigms of justice based on economic redistribution and the recognition of group identities.